(untitled) (Research, Society and Development, 2021)
In order to evaluate the potential of a new fluid capable of improving the efficiency of thermal exchange processes in refrigeration systems, the present work proposed the study of the thermo-hydraulic performance of nanofluids constituted by nanoparticles of carbon nanotubes of the type MWCNT dispersed in distilled water. Nanoparticles with -OH functionalization degree, 3%, 6% and 9% were used to produce nine samples of nanofluids. The “two-step” method, with the help of sonication and high-pressure homogenization, was used to disperse the nanoparticles in the base fluid. To evaluate the thermo-hydraulic performance, the following steps were performed: production of the nanofluids by the two-step method. The use of the experimental bench allowed to obtain the necessary parameters for the determination of the heat transfer coefficient by convection and thermohydraulic performance.